2022
DOI: 10.1186/s12903-021-02035-8
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of a deep learning approach to detect marginal bone loss around implants

Abstract: Background Recently, there has been considerable innovation in artificial intelligence (AI) for healthcare. Convolutional neural networks (CNNs) show excellent object detection and classification performance. This study assessed the accuracy of an artificial intelligence (AI) application for the detection of marginal bone loss on periapical radiographs. Methods A Faster region-based convolutional neural network (R-CNN) was trained. Overall, 1670 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 43 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…Several deep learning studies related to dental implants have been reported. The marginal bone loss around implants has also been extensively studied [ 17 , 18 ]. Liu et al used a balanced database, but the incidence of bone resorption at implant margins was low [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several deep learning studies related to dental implants have been reported. The marginal bone loss around implants has also been extensively studied [ 17 , 18 ]. Liu et al used a balanced database, but the incidence of bone resorption at implant margins was low [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The marginal bone loss around implants has also been extensively studied [ 17 , 18 ]. Liu et al used a balanced database, but the incidence of bone resorption at implant margins was low [ 17 ]. And there was a need to improve model performance through standardized radiographs produced via the paralleling technique.…”
Section: Discussionmentioning
confidence: 99%
“…The mask R‐CNN strategy was created based on Quicker R‐CNN to distinguish targets on images and provide high‐quality division and segmentation [76]. In addition, as stated by Liu, an AI framework based on Speedier R‐CNN examination of periapical radiographs could be a promising assistant demonstrative apparatus for peri‐implant bone loss discovery [77]. The Faster R‐CNN model could be used for comparative analysis in association with the implant detection task.…”
Section: Application Of Ai In Implantologymentioning
confidence: 99%
“…In 2022, Liu et al use R-CNN to detect marginal bone loss around dental implants ( Liu et al, 2022 ). They find that their model output performs similarly to the resident dentist but is less accurate than the experienced dentist.…”
Section: Related Workmentioning
confidence: 99%